A Multidisciplinary Education Framework to Adopt IT Undergraduates in non-IT Disciplines - Amca, Hasan; Elci, Alev (Cyprus Academic Forum, 1st All Cyprus Social Sciences and Humanities Conference / Nicosia , Cyprus., 2005)
Computing and Information Technology (IT) skills became more and more desirable for many non-IT disciplines such as, Communication and Media Studies, Education, and Economy. Therefore, a new multidisciplinary education framework is required, in which the students IT skills will be developed along with the soft skills before they are transferred to the education environment to develop their professional skills. This is due to the need to satisfy the industries requirements. We propose an effective and economically feasible educational framework where the graduates from the Information Technology departments, fully proficient in data collection, processing and management besides system analysis skills, would continue their graduate/postgraduate education in non- IT disciplines. Such students will have completed, without wasting any time, the deficiency programs through the use of free-elective courses which are already available in their curricula.
Keywords: Computing and Information Technology; non-IT disciplines; multidisciplinary education framework; transdisciplinary education; system analysis skills; graduate/postgraduate education in non- IT disciplines